2021
DOI: 10.1245/s10434-021-10925-y
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Combined Peritoneal and Local Treatment for Patients with Peritoneal and Limited Liver Metastases of Colorectal Origin: A Systematic Review and Meta-Analysis

Abstract: Background Almost half of all colorectal cancer (CRC) patients will experience metastases at some point, and in the majority of cases, multiple organs will be involved. If the peritoneum is involved in addition to the liver, the current guideline-driven treatment options are limited. The reported overall survival ranges from 6 to 13 months for the current standard of care (systemic treatment). This study aimed to evaluate morbidity and clinical long-term outcomes from a combined local treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The outcomes of patients with CRLMs and peritoneal metastases evaluated in this study correlate to the results of previous studies, where 5-year OS varied from 8 to 25% [ 33 , 55 ]. HIPEC combined with CRS is considered a standard of care to treat limited peritoneal metastases.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The outcomes of patients with CRLMs and peritoneal metastases evaluated in this study correlate to the results of previous studies, where 5-year OS varied from 8 to 25% [ 33 , 55 ]. HIPEC combined with CRS is considered a standard of care to treat limited peritoneal metastases.…”
Section: Discussionsupporting
confidence: 81%
“…Here, a peritoneal cancer index of < 20 is considered to be limited and therefore signifies a potential curative disease [ 26 , 27 ]. A systematic review by Polderdijk et al states that a 5-year OS rate of 25% can be achieved when combining local treatment of limited CRLM and CRS-HIPEC in selected cases with a previous response to systemic therapy [ 55 ]. Current national guidelines advise a maximum of three CRLMs present when considering a combined treatment strategy with local treatment of CRLM and CRS-HIPEC of peritoneal metastases [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence suggests that CRS ± IPCT may benefit patients with limited extraperitoneal disease, but it requires careful consideration [39]. A recent systematic review of 20 studies revealed a mean overall survival of 26.4 months and a 5-year overall survival rate of 25% in patients receiving combined peritoneal and local treatment for peritoneal and limited liver metastases [40]. Our consensus recommends avoidance of major hepatectomy with CRS.…”
Section: Resultsmentioning
confidence: 99%
“…Patients have been found to respond well to this treatment, with median overall survival (OS) rates increasing to between 20 and 63 months and 5-year OS rates of 23–52% [ 10 , 11 ]. Specific outcomes are associated with various factors representing the severity of the disease, including the peritoneal cancer index (PCI), the completeness of cytoreduction (CC), and tumor histopathology [ 12 ]. The success of CRS + HIPEC is dependent on the careful selection of suitable patients (e.g., PCI < 20), in whom the combined therapy has been reported to be better than the best current systemic chemotherapies [ 13 ].…”
Section: Introductionmentioning
confidence: 99%